A Study on Impact of Rare Earth Elements and Bacteria in Growth of Wheat (Triticum aestivum) - and P. Saranraj1, S. Anitha1*, E.S. Challaraj Emmanuel2 (Journal of Ecobiotechnology, 2010)
Abstract <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;"><span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">The present study was investigated to study the impact of Rare earth elements in growth of wheat. The soil samples were collected from rare earth environments and analyzed by ICP-MS to know constituents of the rare earth elements. Cerium and Neodymium are abundant in the analyzed samples. The physical parameters of the wheat biomass are evaluated with and without treatment of REEs and also treated with REEs and a bacterial strain (Pseudomonas sp.,). From the results it is evident that a significant increase in root and shoot length, dry weight and wet weight of plants treated with REEs. The production stress resistant end product (phenol) is measured and the total content of soluble phenols is calculated. Seeds treated with element alone show two fold increases in the production of phenol. The diverse parts of plant samples (root, shoot and leaves) are digested analyzed by ICP-OES analysis. It reveals that a maximum accumulation of REEs (Cerium and Neodymium) in plant tissues and higher input of REEs yields high accumulation and lower inputs yield low accumulation. The seeds treated with culture are shown drastic change in the accumulation of REEs by wheat. --- 1Department of Microbiology, Annamalai University, Annamalainagar Â 608 002, India 2Department of Microbiology, Sourashtra College, Madurai â€“ 625 00, India